Penjor Sebagai Simbol Pencitraan Diri Umat Hindu di Kota Mataram - I Wayan Sutama (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2020)
In contemporary development, the penjor is increasingly being used both as a means of religious rituals and as a profane means. This research focuses on 3 questions 1). What is the process of the emergence of penjor in the city of Mataram? 2). What are the types, functions, and meanings of penjor in the city of Mataram? 3). How is penjor a symbol of the self-image of Hindus in the city of Mataram? This study uses a qualitative descriptive approach that emphasizes the interpretation of denotative and connotative meanings by using the theory of symbolic and semiotic interactionism. Data collection techniques by observation, interview, literature study, and documentation. The results of the analysis include: 1) The appearance of penjor in the city of Mataram began with the history of the attack of the Karangasem kingdom to Lombok. The increasingly safe situation of Lombok encourages the transfer of the Karangasem community to Lombok which carries Balinese Hindu traditions, including penjor, 2) Penjor is divided into 2 types namely ceremonial penjor and ornamental penjor. Penjor ceremony is made from bamboo with curved edges, the trunk is decorated with Ambu (young palm leaves) or Busung (young coconut leaves) filled with accessories. Penjor ceremony functioned as a means of religious rituals (god yadnya) and Manusa yadnya. The meaning of penjor symbolizes the mountain and its contents where the gods come from, as a form of expression of gratitude for the gift given by God and the celebration of Galungan. The commodification of penjor in the city of Mataram is still in a standard form but has begun to use a combination of natural and synthetic ingredients. 3) Penjor is a symbol of the self-image of Hindus, showing internal solidarity with other Hindus and externally to present the front stage as a Hindu that refers to the aesthetic and artistic values ​​of religious ritual symbols that contain the values ​​of the Satyam, Siwam, Sundaram.